A Missense Mutation (Tyr88 to Cys) in the Platelet Membrane Glycoprotein Ibβ Gene Affects GPIb/IX Complex Expression - Kurokawa, Yumi; Ishida, Fumihiro; Kamijo, Takehiko; Kunishima, Shinji; Kenny, Dermot; Kitano, Kiyoshi; Koike, Kenichi (Thrombosis and Haemostasis, 2001)
This study examined the molecular basis of a missense mutation of the platelet glycoprotein (GP) Ibβ gene in two families. In the propositus with a novel form of Bernard-Soulier syndrome (BSS) from Family I, only GPIbα was detectable in reduced amounts on platelet surfaces by flow cytometry. There were no GPIX or GPIbβ found by immunoblotting. DNA sequencing analysis showed a homozygous mutation in the GPIbβ gene which changed Tyr (TAC) to Cys (TGC) at residue 88. Her parents were heterozygous for Tyr88Cys in the GPIbβ gene. In transient transfection studies on 293T cells, both Tyr88Cys and Tyr88Ala mutations suppressed the expression of GPIb/IX complexes. In addition, Tyr88Cys GPIbβ mutation was found to exert a dominant negative effect on the GPIb expression.Five individuals from Family II, four of whom reported elsewhere as having giant platelet disorders with normal aggregation (BLOOD, 1997; 89: 2404) and one newly analyzed in this study, were heterozygous for Tyr88Cys in the GPIb gene. Microsatellite analysis of chromosome 22 showed a common haplotype in 8 of the individuals with Tyr88Cys mutations in Families I and II. Tyr88 in the GPIbβ gene plays a significant role in the GPIb/IX expression; the defect causes BSS in a homozygous form and possibly giant platelets in a heterozygous form.
Keywords: Bernard-Soulier syndrome; platelet glycoprotein; Ibbeta; missense mutation; dominant negative